1994
DOI: 10.1136/fn.70.2.f137
|View full text |Cite
|
Sign up to set email alerts
|

Diet and faecal flora in the newborn: nucleotides.

Abstract: Breast milk contains nucleotide salts that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…However, the data are conflicting (Balmer et al, 1994;Ostrom et al, 2002). There are few data from well-controlled RCTs to demonstrate that NT supplementation of term infants protects against infection.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the data are conflicting (Balmer et al, 1994;Ostrom et al, 2002). There are few data from well-controlled RCTs to demonstrate that NT supplementation of term infants protects against infection.…”
Section: Discussionmentioning
confidence: 98%
“…However, other RCTs have been unable to confirm the reported beneficial effects of NT supplementation (Balmer et al, 1994;Woltil et al, 1995;Yau et al, 2003). Many of the trials had small sample sizes and inadequate information to assess trial quality, hence making it difficult to establish the clinical efficacy of NT supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have examined the effect of supplementing formula with those compounds on intestinal structure of the neonate. The effects of nucleotide-supplemented formulas on infant microbiota are contradictory: some clinical trials observed a bifidogenic effect of nucleotides on faecal microbiota (103) while others did not (104) . Intestinal permeability and pancreatic enzyme secretion were also not modified by the addition of nucleotides in the formula of neonates (66,85) .…”
Section: Nucleotidesmentioning
confidence: 99%
“…Original data from ref. 9. in the formula-fed groups, bacteroides enterococci and coliforms were more common (9).…”
Section: Faecal Floramentioning
confidence: 99%